1969
DOI: 10.1084/jem.129.5.953
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for Continuous Antigenic Stimulation in the Development and Differentiation of Antibody-Forming Cells

Abstract: The levels of both antigen and specific immunoglobulin are considered important regulatory mechanisms which determine the size of the antibody-producing cell compartment. Uhr and Finkelstein (1) demonstrated that the presence of antigen is essential for continuous synthesis of 19S antibody at any stage after its initiation. Recent studies suggest that repeated antigen contact of immunocompetent cells is required for complete differentiation (2-4). The X-Y-Z immune cell maturation scheme of Sercarz and Coons (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1971
1971
1976
1976

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…The early development of memory reported here agrees with the observations of other workers who have studied the 2 ° humoral or cellular responses to erythrocyte antigens (2,9,25,26). In contrast to these results is the length of time taken for memory to develop to some protein antigens (1,4).…”
Section: Table III Immunological Activity Of Srbc-primed T and B Lympsupporting
confidence: 82%
See 3 more Smart Citations
“…The early development of memory reported here agrees with the observations of other workers who have studied the 2 ° humoral or cellular responses to erythrocyte antigens (2,9,25,26). In contrast to these results is the length of time taken for memory to develop to some protein antigens (1,4).…”
Section: Table III Immunological Activity Of Srbc-primed T and B Lympsupporting
confidence: 82%
“…Using these criteria, it has been demonstrated that priming for a 2 ° response to sheep erythrocytes (SRBC) in mice occurs during a 4-5 day period after immunization (2,3). For other antigens, the development of memory may be a longer process (1,4) and the long-term persistence of antigen may be an important requirement, as it may also be for the maintenance of memory (5).…”
Section: (From the Department Of Zoology Edinburgh University Edinbmentioning
confidence: 99%
See 2 more Smart Citations
“…The immunological memory generated by intra venous immunization with alum-precipitated bovine serum albumin (AP-BSA) developed with time through the following threephases: (a) the early phase in which the memory forIgM antibody response (IgM memory) was generated within a few days after immunization, (b) the intermediate phase (from a few days up to about a month after immunization) in which IgG memory grew andIgM memory decreased, and (c) the late phase in which only IgG memory persisted but progressively degenerated (from than a month afterimmunization). Such a process may be applicable to the immunological memory for many other thymus-dependent antigens [2,8,27,31].…”
mentioning
confidence: 99%